Dynamic fiber-optic shape sensing using fiber segment interferometry - Kissinger, Thomas; Chehura, Edmond; Staines, Stephen E.; James, Stephen W.; Tatam, Ralph P. (Cranfield University, 2017)
Research Data for Paper "Dynamic fibe- optic shape sensing using fiber segment interferometry" by Thomas Kissinger, Edmond Chehura, Stephen E. Staines, Stephen W. James and Ralph P. Tatam, Cranfield University, UK
Keywords: Optical interferometry,'; 'Vibrometry'; 'Shape measurement'; 'Shape Sensing'; 'Curvature Sensing'; 'Bend Sensing'; 'Condition monitoring'; 'Structural Health Monitoring'; 'Optical Fibre Sensing'; 'Photonics and Electro-Optical Engineering (excl. Communications)'; 'Dynamics; Vibration and Vibration Control'